Clinical and subclinical vitamin D deficiency in Bradford children. Issue 12 (December 1976) - Ford, J A; McIntosh, W V; Butterfield, R; Preece, M A; Pietrek, J; Arrowsmith, W A; Arthurton, M W; Turner, W; O'Riordan, J L; Dunnigan, M G
Abstract : A survey of the vitamin D status of Bradford schoolchildren was carried out in April 1973, employing conventional biochemistry, radiology, and measurement of 25-hydroxycholecalciferol levels. Biochemical evidence of rickets was present in 45% of the Asians. When re-examined in September, several children showed spontaneous biochemical resolution; nevertheless, radiological abnormalities were present in 12% of the original sample. No evidence of rickets was detected in the smaller White sample. Minor biochemical abnormalities were present in 9 of the 40 West Indian children. A study of admissions of Bradford hospitals in the 4 years 1969-1972 inclusive confirmed that clinical vitamin D deficiency was confined to Asians except for a few cases of infantile rickets in White children. The probability that one Asian child in 40 may require admission during the period from birth to adolescence emphasizes the urgent need for the introduction of prophylactic measures.